2022
DOI: 10.1121/10.0009160
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic jet noise from launch vehicles: 50 years since NASA SP-8072

Abstract: In 1971, the U.S. National Aeronautics and Space Administration (NASA) published a seminal report—NASA SP-8072—which compiled the results of the early supersonic jet noise studies and provided methods to calculate the noise produced from launch vehicles. Fifty years later and despite known limitations, SP-8072 remains the foundation for much of the launch vehicle noise modeling today. This article reviews what has been learned about the physics of noise generation and radiation from free and impinging rocket p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 242 publications
0
17
0
Order By: Relevance
“…Dhamanekar and Srinivasan's findings revealed that the central protrusion on the impinging plate exhibits greater efficacy in attenuating tones within supersonic impinging jets compared to those present in subsonic impinging jets. 38 Recently, Lubert et al 39 conducted a comprehensive review of the research conducted by NASA over the past 50 years on the physics underlying the generation and mitigation of noise from launch vehicles. Different noise reduction techniques for impinging jets can be found in the review articles of Jiang et al, 5 and Salehian and Mankbadi.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…Dhamanekar and Srinivasan's findings revealed that the central protrusion on the impinging plate exhibits greater efficacy in attenuating tones within supersonic impinging jets compared to those present in subsonic impinging jets. 38 Recently, Lubert et al 39 conducted a comprehensive review of the research conducted by NASA over the past 50 years on the physics underlying the generation and mitigation of noise from launch vehicles. Different noise reduction techniques for impinging jets can be found in the review articles of Jiang et al, 5 and Salehian and Mankbadi.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…There exist many limitations of the current understanding of the acoustic sources during a rocket launch (Lubert et al). 6 A phased array can be a very useful tool in filling these voids.…”
Section: Introductionmentioning
confidence: 99%
“…These waves propagate to the launcher fairing, where they exert strong acoustic loads likely to damage the payload. The sound fields near the rocket structure thus require a specific attention from the aerospace industry, as highlighted in the review by Lubert et al [1]. In order to characterize them, the impingement of the gases exhausted by the engines on the launchpad can be modeled as a jet impinging on a flat plate.…”
Section: Introductionmentioning
confidence: 99%